Technology sourcing and the dark side of open innovation: Evidence from the biopharmaceutical sector. (January 2023) - Purdy, Lauren; Eslami, Hadi; Eshghi, Kamran; Rod, Michel
Abstract: Firms in high-technology industries face a complex set of challenges to innovate successfully and continuously to gain a sustainable competitive advantage. Innovative new R&D project sourcing choices top this list of difficult and nuanced choices that firms must make in pursuit of innovation. Our research makes a significant and novel contribution to this interesting discourse and critically examines the sourcing decision (i.e., open vs. closed innovation) in the context of new product development in the biopharmaceutical sector. Specifically, we apply a project-level typology along the dimensions of new R&D project source and project familiarity. Drawing from transaction cost economics (TCE) and the knowledge-based view (KBV) theories, we empirically test our theoretically developed hypotheses on a dataset of 2, 971 biopharmaceutical R&D projects spanning from 1985 to 2016. Results from our robust analysis show that both new R&D project source and project familiarity have significant direct effects on focal project performance outcomes (defined in this paper as likelihood of termination). We also determine that focal project familiarity has a significant moderating effect on the relationship between project source and performance outcome. Highlights: We examine firms' open innovation sourcing decisions and project-level performance outcomes. Projects sourced via open innovation are associated with a higher likelihood of termination. Projects in knowledge areas that are familiar to the firm are less likely to be terminated. Familiarity with a project's knowledge area has a mitigating effect on the risks of external sourcing.